2019
DOI: 10.1089/trgh.2019.0021
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Transgender and Gender Nonbinary Medical Students and Physicians

Abstract: To explore the experiences of transgender and gender nonbinary (TGNB) medical students and physicians in the United States. Methods: The authors conducted a 79-item online survey using Likert-type and open-ended questions to assess the experiences of TGNB-identified U.S. medical students and physicians. Variables included demographic data, disclosure of TGNB status, exposure to transphobia, and descriptions of educational and professional experiences. Recruitment was conducted using snowball sampling through L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
83
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 31 publications
2
83
0
4
Order By: Relevance
“…A recent study examined experiences of TGNB medical students and physicians. 12 The researchers found that 22% of participants reported barriers attributable to their gender identity while applying to medical school and 43% while applying for residency. They also found that 78% of participants censored themselves during training to avoid disclosing their TGNB identity and that 69% heard derogatory comments about TGNB individuals during their training or practice.…”
Section: Experiences Of Transgender and Gender Nonbinary Trainees Andmentioning
confidence: 99%
“…A recent study examined experiences of TGNB medical students and physicians. 12 The researchers found that 22% of participants reported barriers attributable to their gender identity while applying to medical school and 43% while applying for residency. They also found that 78% of participants censored themselves during training to avoid disclosing their TGNB identity and that 69% heard derogatory comments about TGNB individuals during their training or practice.…”
Section: Experiences Of Transgender and Gender Nonbinary Trainees Andmentioning
confidence: 99%
“…A transgender person's gender identity differs from sex assigned at birth, and nonbinary people have a gender identity outside the traditional male/female binary. 1,2 US prevalence of transgender and nonbinary (TNB) people is 0.3 to 2.7%, [3][4][5] and the Association of American Medical Colleges reports rising matriculation of TNB medical students, from 596 in 2016 to 1010 in 2018. 6 Thus, increasing numbers of TNB students are applying for residency positions.…”
Section: Introductionmentioning
confidence: 99%
“…In a 2019 report, 60% of physicians did not disclose their gender identity to residency programs due to lack of perceived support, discrimination fears, or not yet understanding themselves as TNB. 2 About half of medical students do not disclose their gender identity during medical school. 7 TNB applicants are vulnerable to discrimination if they have not legally changed their name and gender, or do not adopt societally expected gender expressions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations